Cathode candidates for zinc‐based thermal‐electrochemical energy storage. (1st September 2015) - Holubowitch, Nicolas E.; Manek, Stephen E.; Landon, James; Lippert, Cameron A.; Odom, Susan A.; Liu, Kunlei
Summary: An electrochemical cell utilizing a molten salt eutectic electrolyte (ZnCl2 –KCl) is investigated as a new low‐cost energy storage technology. Using Zn as the anode, a broad range of candidate cathode materials (Al, Ag, Bi, C, Cu, a Ni alloy, Sn, and Pb) are characterized by open‐circuit potential, chronoamperometry, and electrochemical impedance spectroscopy methods. Cells employing the molten metal cathodes Sn, Bi, and Pb deliver markedly high current densities independent of their standard reduction potentials. Molten Pb (at 330 °C), for example, gave 25 times higher current density than solid Pb (at 315 °C). Additionally, ZnCl2 –KCl is employed for the first time in an energy storage application and it affords an operating temperature >100 °C lower than other liquid metal battery technologies. Thermal properties of this relatively air‐stable molten salt electrolyte allow for a second mode of energy storage, that is, thermal. The combination of an inexpensive Zn anode, low‐temperature eutectic electrolyte, and a molten metal cathode offers a simple and promising electrochemical system for dual‐mode (thermal‐electrochemical) large‐scale energy storage. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : An electrochemical cell utilizing a molten salt eutectic electrolyte is investigated as a new low‐cost energy storage technology. Using Zn as the anode, multiple cathode candidates were screened. Cells employing molten metal cathodes that alloy with Zn delivered markedly high current densities independent of their standard reduction potentials and show promise for grid storage.